INVENTARISASI TUMBUHAN PAKU DI KAMPUS I UNIVERSITAS MEDAN AREA - JUBAIDAH NASUTION; JAMILAH NASUTION; EMMY HARSO KARDHINATA (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2017)
Inventory of ferns in the University of Medan Area subdistrict Percut Sei Tuan district of Deli Serdang North Sumatra. Ferns generaly live in moist place and open. In the campus of the University of Medan Area 1 has a variety of tree, thus enabling the discovery of epiphytic and terrestrial nails done in campus of the University of Medan Area. The method used in this research is descriptive exploration techniques and documentation, that one the rescarch by describing an object without exaggerated. The sample used in the total sample using purposive sampling method. The results obtained many as 15 species consist of 11 epiphytic ferns are (Davallia trichomanides, Nephrolepis hirsutula, Asplenium nidus, Pyrrosia piloselloides, Pyrrosia lanceolata, Tectaria sp, Drymoglossum piloselloides, Drynaria quercifolia, Selliguea sp, Goniophlebium verrucosum, Vittaria elongata), and four terrestrial namely (Adiantum trafeziforme, Acrostichum aureum, Lygodium circinnatum, Thelypteris sp)